Epidemiological analysis of benign and malignant salivary gland tumors in Peshawar: a retrospective study from tertiary care hospitals (2020–2024) - Khan, Hayat Ullah; Iqbal, Fatima; Masood, Bilal; Ullah, Azmat (International Journal of Pathology, 2025)
Background: Salivary gland tumors are rare lesions that pose diagnostic and therapeutic challenges due to their histological diversity and variable behavior. This study aimed to characterize the demographic and clinicopathological features of primary salivary gland tumors treated at two tertiary centers in Peshawar, and to assess associations between tumor behavior and patient age, sex, and tumor site. Methods: We conducted a retrospective review of 272 patients treated for primary salivary gland tumors at two tertiary centers in Peshawar between January 2020 and December 2024. Patient demographics, tumor site, histological subtype, and behavior were extracted from pathology reports and clinical records. Statistical associations between tumor type and age, sex, and anatomical location were assessed with p < 0.05 indicating significance. Results: The cohort included 147 women (54.0%) and 125 men (46.0%), with a mean age of 45 years (range 0–100 years). Benign tumors comprised 74.6% (n = 203), most frequently arising in the parotid gland (76.5%), whereas malignant tumors accounted for 25.4% (n = 69) and were disproportionately found in minor salivary glands (33.3% malignant). Pleomorphic adenoma was the leading benign subtype (70.4%), and mucoepidermoid carcinoma was the predominant malignancy (26.1%). Malignancy rates increased with age, rising from 7.7% in patients under 20 to 100% in those over 80 (p = 0.006). No significant gender differences in tumor behavior were observed (p = 0.48), but the distribution of sexes varied across age groups. Conclusion: Younger patients with small, asymptomatic lesions may be managed conservatively, while older patients and those with minor gland tumors warrant prompt biopsy and cytological evaluation. Prospective, multicenter registries are essential to refine these observations and guide resource allocation in similar settings.